PENGARUH MOTIVASI KERJA, KEPEMIMPINAN, LINGKUNGAN KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR DAN KEPUASAN KERJA DI PT. SUCOFINDO - DAVID PRASETYO SOENTORO, DAVID PRASETYO SOENTORO DAVID PRASETYO SOENTORO (Kajian Ilmiah Mahasiswa Manajemen, 2013)
In the era of globalization, the company is required to have good performance in order to survive in the midst of a very tight competition between organizations. Any company or organization to carry out activities to achieve the goals set before the attempt to gain an advantage, but not apart from its main purpose is to prosper and provide job satisfaction for the employees so that the company is also getting feedback gained from the ability of its employees because the employee is asset for the company. The purpose of this study was to determine the effect of Job motivation, leadership, work environment on organizational citizenship behaviors and job satisfaction in the PT. SUCOFINDO. Type of research is causal research, this study consisted of variable exogenous and endogenous. Exogenous variables of this study is motivation, leadership, and work environment while endogenous variables are organizational citizenship behaviors and job satisfaction. The research sample set at 134 samples and data analysis techniques using Structural Equation Modeling. The results of this study indicate that the motivation had no effect on organizational citizenship behavior, but influence on job satisfaction, leadership, organizational citizenship behavior affects and job satisfaction, work environment had not effect on organizational citizenship behavior, but influence on job satisfaction, and organizational citizenship behavior does not affect the job satisfaction.